(untitled) (Lectio: Journal of Language and Language Teaching, 2026)
This study aims to systematically analyze the integration of digital technology in Indonesian learning in economic contextual context through the Computer-Assisted Language Learning (CALL) approach. The background of this research departs from the urgent need to increase the effectiveness of language learning in the era of digital transformation, especially in the context of economic education that demands high communication skills and digital literacy. The method used is Systematic Literature Review (SLR) based on the PRISMA guidelines, by examining 35 scientific articles published between 2019 and 2025 from the Scopus, ScienceDirect, Google Scholar, and ERIC databases. The analysis process is carried out through thematic analysis which includes the identification of CALL innovation trends, the impact on learning outcomes, and implementation challenges in the regions. The results show that the integration of digital technology through CALL significantly improves students’ learning motivation, critical thinking skills, and understanding of the economic context. CALL also strengthens contextual learning by providing economic simulations and digital project-based activities relevant to the world of work. However, several main obstacles were found, such as limited infrastructure, a gap in teachers’ digital literacy, and a lack of technology-based pedagogical training. This study confirms that effective implementation of CALL requires an integrative strategy between curriculum, teacher competence, and sustainable technology support. The results of this SLR are expected to be a conceptual basis for the development of an economic context-based Indonesian learning model in the digital era, as well as strengthen the direction of national education policies towards adaptive and innovative learning.